The main problems of insulating coatings of main pipelines - Utepbergenova Лаура; Aitmukasheva Айым (Рroblems of engineering and professional education, 2023)
This article examines the system of trunk pipelines, which lead to the actual importance of the country’s economy, the work carried out to counter damage to the environment and the effectiveness of protection against corrosion.